Parenteral Nutrition in Liver Resection. (29th March 2012) - Chiarla, Carlo; Giovannini, Ivo; Giuliante, Felice; Ardito, Francesco; Vellone, Maria; De Rose, Agostino Maria; Nuzzo, Gennaro
Abstract : Albeit a very large number of experiments have assessed the impact of various substrates on liver regeneration after partial hepatectomy, a limited number of clinical studies have evaluated artificial nutrition in liver resection patients. This is a peculiar topic because many patients do not need artificial nutrition, while several patients need it because of malnutrition and/or prolonged inability to feeding caused by complications. The optimal nutritional regimen to support liver regeneration, within other postoperative problems or complications, is not yet exactly defined. This short review addresses relevant aspects and potential developments in the issue of postoperative parenteral nutrition after liver resection.